2018
DOI: 10.3389/fphys.2017.01135
|View full text |Cite
|
Sign up to set email alerts
|

Increased Contractile Function of Human Saphenous Vein Grafts Harvested by “No-Touch” Technique

Abstract: Saphenous vein grafts are the most common conduits used for coronary artery bypass grafting (CABG); however, no more than 60% of vein grafts remain open after 10 years and graft failure is associated with poor clinical outcome. The “no-touch” harvesting technique—where a sheet of perivascular tissue is retained around the vein—improves graft patency to over 80% after 16 years of follow-up, but the mechanism for the improved patency rate is unclear. In this study, we investigated acute functional differences be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Such issues may be difficult to address when using organ bath studies as described by Yamada et al [ 1 ] and others [ 4 , 6 , 7 ] , but they may perhaps be elucidated using the myograph preparation, although this is technically more challenging. In fact, using this technique, Vestergaard et al [ 44 ] showed a tendency toward improved vasorelaxation of NTSV compared to CTSV ( Figure 3 ), but this improvement was just below statistical significance. However, as some NTSVs examined were manually distended (no details provided) and some were not distended, it is not clear if both distended and non-distended NTSVs were analysed together as one group.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Such issues may be difficult to address when using organ bath studies as described by Yamada et al [ 1 ] and others [ 4 , 6 , 7 ] , but they may perhaps be elucidated using the myograph preparation, although this is technically more challenging. In fact, using this technique, Vestergaard et al [ 44 ] showed a tendency toward improved vasorelaxation of NTSV compared to CTSV ( Figure 3 ), but this improvement was just below statistical significance. However, as some NTSVs examined were manually distended (no details provided) and some were not distended, it is not clear if both distended and non-distended NTSVs were analysed together as one group.…”
mentioning
confidence: 90%
“…The vein grafts (n = 13-14) were stretched to an internal diameter corresponding to a transmural pressure of 20 or 100 mmHg, pre-contracted with 10 µM serotonin, and exposed to 10 µM methacholine. It is acknowledged that this diagram is from the Open Access article Vestergaard et al [ 44 ] , 2018. PVT=perivascular tissue.…”
mentioning
confidence: 99%
“…2,5À7 Histological and immunohistochemical studies have demonstrated improved integrity of endothelium and smooth muscle cells. 8,9 Furthermore, NT-SVGs have been shown to preserve contractile function in contrast to C-SVGs in myographic studies. 10 A recent network meta-analysis of randomized controlled trials comparing patency of second conduit grafts encouraged the use of NT-SVGs over arterial grafts.…”
Section: Introductionmentioning
confidence: 99%
“…6) Previous study showed "no-touch" harvest vein grafts presented with tone regulation on the vascular wall in vitro. 7) However, little is known about its altered vasomotor performance in vivo experiment and consequences of different vein harvest techniques for vasomotor development after intraluminal administration of anti-spastic medication have not been previously evaluated. We proposed that higher baseline blood flow and less dynamic fluctuations were associated with the superior anti-spastic and distension-tolerant function of "no-touch" vein grafts in CABG surgery.…”
Section: Introductionmentioning
confidence: 99%